POLITIK KURIKULUM PAI: ANALISIS KEKUASAAN FOUCAULT DALAM PERUBAHAN KEBIJAKAN PENDIDIKAN ISLAM 2000-2025 - Nurul Izzah (AN-NUR: Jurnal Pendidikan dan Pembelajaran, 2025)
This article explores the dynamics of Islamic Religious Education (PAI) curriculum in Indonesia through the genealogical lens of Michel Foucault, focusing on the interplay between power, discourse, and knowledge. The study identifies how the state, through education policies, teacher training, and institutional structures, produces and reproduces specific forms of religious knowledge deemed legitimate. Employing a critical-qualitative approach and policy document analysis from 2000 to 2025, the research reveals that the PAI curriculum serves not merely as a pedagogical tool but also as a discursive battleground among state ideology, Islamization narratives, and resistance at the implementation level. Through Foucault’s concepts of archaeology and genealogy, the analysis uncovers how terms such as tolerance, moderation, and radicalism are strategically framed within policy to shape perceptions and behavior. The findings highlight a trend of religious thought homogenization enforced by curriculum regulation and the political suppression of interpretive diversity within Islam. Conversely, resistance manifests through practical adjustments and the emergence of alternative discursive spaces beyond formal institutions. This article recommends the need for transparency, public participation, and epistemic pluralism in the formulation of Islamic education policies to foster a more equitable and democratic curriculum framework.